2019
DOI: 10.3390/foods8120594
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Structural Change during In Vitro Digestion of Heated Soy Protein Isolates

Abstract: Use of soy protein isolate (SPI) as the encapsulating material in emulsions is uncommon due to its low solubility and emulsification potential. The aim of this study was to improve these properties of SPI via heat treatment-induced modifications. We modified SPI under various heating conditions and demonstrated the relationship between structure and in vitro digestibility in simulated gastric fluid by means of Sodium Dodecyl Sulphide-Polyacrylamide Gel Electrophoresis (SDS-PAGE) and Raman spectroscopy. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 49 publications
2
15
0
1
Order By: Relevance
“…Moreover, heat-treated groups (80, 100, and 121°C) showed lower degrees of hydrolysis than the control, with a similar tendency across the process of digestion. This is compatible with findings from Tian et al ( 63 ) which showed that the degree of hydrolysis of soy protein isolates reduces after thermal treatment above 85°C. Similarly, Sangsawad et al ( 64 ) also reported that high-temperature treatment at 121°C strongly decreases the digestibility of chicken breast protein.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, heat-treated groups (80, 100, and 121°C) showed lower degrees of hydrolysis than the control, with a similar tendency across the process of digestion. This is compatible with findings from Tian et al ( 63 ) which showed that the degree of hydrolysis of soy protein isolates reduces after thermal treatment above 85°C. Similarly, Sangsawad et al ( 64 ) also reported that high-temperature treatment at 121°C strongly decreases the digestibility of chicken breast protein.…”
Section: Resultssupporting
confidence: 93%
“…In this study, the trend of hydrolysis of QPI after heat treatment was similar to that of untreated QPI, and the hydrolysis of QPI after heat treatment at 90 and 121 °C for 30 min was lower than that of untreated QPI during the whole digestion process, among which the hydrolysis of QPI after treatment at 121 °C was the smallest, which was 25.53% after simulated in vitro digestion for 240 min, significantly lower than that of untreated QPI at 20.64% ( Figure 5 A). Previous studies found that the hydrolysis of soybean isolate protein (SPI) decreased under heat treatment conditions greater than 85 °C [ 54 ]. Reduction in protein digestibility of QPI after heating treatment has generally been attributed to the formation of cross-linked protein polymers, which are resistant to proteolysis [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is commonly thought that a certain extent of heat induced protein denaturation improves the digestibility, while more extensive heat treatment would induce protein aggregation which would, in turn, reduce the digestibility. The work of Tian et al [ 59 ] demonstrates the relation between heating time and temperature, and the extent of pepsin-catalysed hydrolysis of soybean PI. Dispersions heated at 85 °C for 15 min presented the highest DH, while those heated at 70 or 100 °C were hydrolysed to a significantly lesser extent.…”
Section: Post-fractionation Processingmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Summary of digestion assays, sample treatment and measurement from studies investigating the effect of processing on protein digestion. References [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ,…”
mentioning
confidence: 99%